Increasing Business Performance in Property Management by Implementing the Green Habit - David Kiki Baringin MT Samosir; Yvonne Augustine; Ratlan Pardede (Indonesian Journal of Sustainability Accounting and Management, 2023)
The objective of this study is to analyze the impact of green habits on property management business performance in Indonesia. This research is relatively new because the variable used, that is the green habit. The data used are the primary data in accordance with a mixed methods approach. The research findings have proven that green habits have a significant influence on business performance, which means green habits can improve business performance. Consumer habits toward environmental sustainability are the determinants of product sales and will ultimately have an impact on increasing sales and company performance. The results of this study contributed both scientific and practical aspects. From the scientific aspect, it supports the theory of organizational behavior, in which companies can run more effectively and influence performance improvement by applying science or something new that is useful. From the practical aspect, the company not only pays attention to profits but must pay attention to environmental aspects and the community around the company, especially property management. It is time to implement sustainability, one of which is green habits so that they can be more developed by increasing business performance and competitiveness.